Antimicrobial Activities of Propolis in Poloxamer Based Topical Gels - Seong-Hyeon An; Eunmi Ban; In-Young Chung; You-Hee Cho; Aeri Kim (MDPI AG, 2021)
Propolis contains a group of compounds with various activities. However, their low solubility is a drawback for the development of pharmaceutical formulations. In this study, poloxamers as a solubilizer and gelling agent were evaluated to develop a topical antimicrobial formulation of propolis. The effects of poloxamer type and concentration on the propolis solubility, release rate, and antimicrobial activities were investigated. Staphylococcus aureus (S. aureus) and Candida albicans (C. albicans) were the representative bacteria and fungi, respectively. At 5%, poloxamer 407 (P407) and poloxamer 188 (P188) enhanced the propolis solubility by 2.86 and 2.06 folds, respectively; at 10%, they were 2.81 and 2.59 folds, respectively. The micelle size in the P188 formulation increased in the presence of propolis, whereas there was no change in the P407 formulation. Release rates of propolis decreased with the P188 concentration increase, which was attributed to viscosity increase. Both P188 and P407 formulations showed antimicrobial activity against S. aureus in a time-kill kinetics assay. However, only the P188 formulation reduced the cell's numbers significantly against C. albicans, compared to the control. We speculate that P188 mixed micelles were more effective in releasing free active compounds to exhibit anti-microbial activity compared to the P407 micelles encapsulating the hydrophobic compounds in their cores. Propolis in P188 formulation is proposed as a potential topical antimicrobial agent based on its activity against both S. aureus and C. albicans.